Production of Human Milk Fat Substitutes by Interesterification of Tripalmitin with Ethyl Oleate Catalyzed by Candida parapsilosis Lipase/Acyltransferase. (24th June 2019) - Tecelão, Carla; Perrier, Véronique; Dubreucq, Eric; Ferreira‐Dias, Suzana
Abstract: In human milk fat, the saturated fatty acids, namely palmitic acid, are located at the sn ‐2 position of triacylglycerols (TAG) while unsaturated fatty acids (e.g. oleic acid) are esterified at position sn ‐1, 3. Thus, sn‐ 1, 3‐dioleoyl‐2‐palmitoylglycerol (OPO) is the target TAG to be used as human milk fat substitutes (HMFS) in infant formulas. In this study, the noncommercial recombinant lipase/acyltransferase from Candida parapsilosis (CpLIP2) was immobilized in Accurel MP1000, and used as a biocatalyst for the interesterification of tripalmitin with ethyl oleate in a solvent‐free medium, to obtain structured lipids used as HMFS. Different molar ratios (MR) of ethyl oleate to tripalmitin (2:1–8:1) were used. After 4 h reaction at 60°C, about 30 mol% of oleic acid incorporation was already observed for all tested MR. An apparent equilibrium was reached after 8–24 h, with 32–51 mol% final incorporation, increasing with the MR. The incorporation of oleic acid into TAG was compared with the maximum predicted values when a random or a sn ‐1, 3‐regioselective biocatalyst was used. The obtained values are consistent with the maximum incorporation expected for a sn‐ 1, 3‐regioselective enzyme. In fact, the amount of oleic acid at position sn ‐2 was approximately 15% for all the MR tested, which is explained by the acyl migration phenomenon. CpLIP2 exhibited higher activity than most commercial immobilized lipases (e.g. faster reaction in solvent‐free media, low enzyme load, and low MR needed), and showed a recognized sn ‐1, 3 regioselective behavior.